GSTA1, GSTM1, GSTP1 and GSTT1 polymorphisms in progressive myoclonus epilepsy: A Serbian case–control study. (November 2015) - Ercegovac, Marko; Jovic, Nebojsa; Sokic, Dragoslav; Savic-Radojevic, Ana; Coric, Vesna; Radic, Tanja; Nikolic, Dimitrije; Kecmanovic, Miljana; Matic, Marija; Simic, Tatjana; Pljesa-Ercegovac, Marija
Highlights: GSTT1-null genotype might increase the risk of progressive myoclonus epilepsy (PME). Major antioxidant enzymes (SOD and GPX) activities are increased in PME patients. Glutathione S -transferase genotypes affect oxidative phenotype in PME patients. Abstract: Purpose: Oxidative stress is recognized as an important factor in progressive myoclonus epilepsy (PME). Genetic polymorphism of glutathione S -transferases (GSTs), which are involved in both protection from oxidative damage and detoxification, might alter the capacity for protecting tissues from exogenous and endogenous oxidants. We aimed to assess a possible association between GST polymorphism and PME, as well as, correlation between GST genotypes and oxidative phenotype in PME patients. Methods: GSTA1, GSTM1, GSTP1 and GSTT1 genotypes were determined in 26 patients with PME and 66 controls. Byproducts of protein oxidative damage (thiol groups (P-SH) and nitrotyrosine), superoxide dismutase (SOD) and glutathione peroxidase (GPX) activities were determined. Results: The frequency of GSTA1, GSTM1 and GSTP1 genotypes was not significantly different between PME patients and controls, while individuals with GSTT1 - null genotype were at 5.44-fold higher risk of PME than carriers of GSTT1 - active genotype. Moreover, significant risk of PME was obtained in carriers of both GSTT1-null and GSTM1 - null genotypes. Carriers of combined GSTA1- active and GSTT1-null genotype were at highest, 7.55-fold increased risk of PME. Byproducts of protein damage did not reach statistical significance, while SOD and GPX activities were significantly higher in PME patients then in controls. When stratified according to GST genotype, P-SH groups were significantly lower only in patients with GSTT1 - null genotype in comparison to carriers of active genotype. Only SOD activity was increased in GSTT1 - null when compared to corresponding active genotype. Conclusions: GSTT1-null genotype might be associated with the increased risk and enhanced susceptibility to oxidative stress in PME patients.